Laparoscopic Surgery for Adhesive Small Bowel Obstruction Is Associated With a Higher Risk of Bowel Injury: A Population-based Analysis of 8584 Patients. Issue 3 (September 2017) - Behman, Ramy; Nathens, Avery B.; Byrne, James P.; Mason, Stephanie; Look Hong, Nicole; Karanicolas, Paul J.
Abstract : Objective: We set out to compare the incidence of bowel repair and/or resection in a large cohort of patients with adhesive small bowel obstruction (SBO) managed operatively. Background: Laparoscopic lysis of adhesions for adhesive SBO (aSBO) is becoming more common, yet might increase the risk of bowel injury given the distended and/or potentially compromised small bowel. Methods: We used administrative discharge data derived from a large geographic region, identifying patients who underwent surgery for their first episode of aSBO during 2005 to 2014. Procedure codes were used to determine the exposure: either an open approach or a laparoscopic approach (including procedures converted to open). The primary outcome was incidence of bowel intervention, defined as intraoperative enterotomy, suture repair of intestine, or bowel resection. We estimated the odds of bowel intervention after adjusting for patient and clinical factors. Results: A total of 8584 patients underwent operation for aSBO. Patients undergoing laparoscopic procedures were younger with fewer comorbid conditions. The rate of laparoscopic approaches increased more than 3-fold during the study period (4.3%–14.3%, P < 0.0001). The incidence of bowel intervention was 53.5% versus 43.4% in laparoscopic versus open procedures ( P < 0.0001). After adjustment for potential confounders, the odds of bowel intervention among patients treated laparoscopically versus open was 1.6 (95% confidence interval: 1.4–1.9). Conclusions: Laparoscopic procedures for aSBO are associated with a greater likelihood of intervention for bowel injury and/or repair. This increase might be due to challenges inherent with laparoscopic approaches in patients with distended small bowel. Surgeons should approach laparoscopic lysis of adhesions with a higher level of awareness and use strategies to mitigate this risk. Abstract : Supplemental Digital Content is available in the text